2016
DOI: 10.3390/s16040437
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Chlorophyll Content Estimation of Winter Wheat Based on Visible and Near-Infrared Sensors

Abstract: The leaf chlorophyll content is one of the most important factors for the growth of winter wheat. Visual and near-infrared sensors are a quick and non-destructive testing technology for the estimation of crop leaf chlorophyll content. In this paper, a new approach is developed for leaf chlorophyll content estimation of winter wheat based on visible and near-infrared sensors. First, the sliding window smoothing (SWS) was integrated with the multiplicative scatter correction (MSC) or the standard normal variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 18 publications
(21 reference statements)
1
31
0
Order By: Relevance
“…For most hyperspectral remote sensing applications [23,47,48,[50][51][52][53][54][55][56][57][58][59][60][61][62], the PCA transformations are always conducted at the spectral dimension based on the high degree of spatial similarity between images at different bands. As illustrated in Figure 1, the spectra of leaves have similar fixed absorption features that are due to pigments and water.…”
Section: Principal Component Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…For most hyperspectral remote sensing applications [23,47,48,[50][51][52][53][54][55][56][57][58][59][60][61][62], the PCA transformations are always conducted at the spectral dimension based on the high degree of spatial similarity between images at different bands. As illustrated in Figure 1, the spectra of leaves have similar fixed absorption features that are due to pigments and water.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Some hyperspectral studies have demonstrated that regression models using PCA (over spectral dimension) gave superior results as compared to using VIs [23,[50][51][52][53]59]. For example, Satapathy showed that the retrieved LAI from PCA has higher accuracy (RMSE = 0.137) than the classical NDVI-LAI empirical approach (RMSE = 1.139) [51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant phenotyping based on hyperspectral imaging techniques has been successfully used mainly in discriminate genotypes with different contents of leaf biochemical components. Frequently, the genotypes are screened for differences in content of leaf chlorophyll (Ferri et al, 2004;Wu et al, 2011;Bauriegel and Herppich, 2014;Zhang et al, 2016), anthocyanins (Gitelson et al, 2002;Shi et al, 2012) or nitrogen (Yu et al, 2014). Sytar et al (2015) analyzed the flavonoid contents in the leaves of 30 plant species using the multiplex fluorimetric sensor.…”
Section: Integration Of Hyperspectral Analyses Into Salt-stress Relatmentioning
confidence: 99%
“…In recent years, the method of measurement of chlorophyll relative content based on multi-spectrum has attracted the attention of many researchers, which has applied to many crops, including rice nitrogen fertilizer recommendation [12,13], potato [14,15], wheat [16,17], and corn [18]. Zhang et al [19] proposed the quantitative analysis model for the relation between the leaf relative chlorophyll content and the reflectance spectra through researching the non-destructive testing of leaf chlorophyll content of winter wheat, and preprocessing using MSC and SNV improved the accuracy. Liu et al [20] pointed out that when the plant was in the process of photosynthesis, it mainly absorbed red light and blue light from the sun; two wavelengths of light selected as the characteristic wavelengths light sources were the infrared region (650 nm) and near-infrared region (940 nm); the chlorophyll content of leaves was determined by comparing the light intensity of the reflected light and the transmitted light through the leaves.…”
Section: Design Of the Portable Farmland Information Collection Symentioning
confidence: 99%